Modelling of a new thermal compressor for supercritical CO2 heat pump. (15th December 2016) - Ibsaine, Rabah; Joffroy, Jean-Marc; Stouffs, Pascal
Abstract: A new concept of thermal compressor has been designed by the boostHEAT company. This compressor uses thermal energy provided through the heater instead of mechanical energy to increase the pressure of the heat pump working fluid. The compressor is made up by the following parts: a cylinder with a displacer piston, a heater, a regenerator and a cooler. The heater is connected to the hot part of the cylinder on the one hand and to the regenerator on the other hand. The cooler is connected to the regenerator on the one hand and to the cold part of the cylinder on the other hand. The cold part of the cylinder is connected to the low pressure branch of the heat pump (evaporator) through an automatic inlet valve, and to the high pressure branch of the heat pump (gas cooler) through an automatic exhaust valve. The compressor is intended to replace the conventional mechanical compressor in a CO2 heat pump for the residential heating or combined heat and power market. The main feature of the system is that the working fluid of the thermal engine for compression is the same as the working fluid of the heat pump. The principle of the new thermal compressor and its advantages for heat pump application will be briefly presented. A model of the thermal compressor has been developed and validated. Modelling results related to the regenerator, the piston rod diameter, the size of the adiabatic dead volumes and the working fluid leaks in the annular gap between the cylinder liner and the piston are presented. Highlights: A new concept of thermal compressor is presented. It is intended to replace the usual mechanical compressor in a CO2 heat pump. The working fluid of the engine for compression is the same as for the heat pump. A model of the thermal compressor has been developed and validated. The influence of several design parameters is studied.